La primauté du droit. L'origine du principe et son évolution dans le contexte de la Charte canadienne des droits et libertés - Pratte, Sonia (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
The rule of law is one of the foundations of our society. In England where it first developed, it symbolized the subjection of royal power to new parliamentary supremacy. Towards the end of the 19th century, A.V. Dicey provided the concept with a description expressed in three well-known premisses. As a component of unwritten law in Canada, the rule of law was to experience many interpretations until finally it was enshrined in the preambule of the Canadian Charter. Henceforth a part of the Constitution, it would now acquire a more formal meaning in its applications to parliaments, administrative acts in general and even to royal prerogatives. Furthermore, the rule also carries with it a content that will be more precisely defined by the courts in years to come. The rule of law now is a dynamic concept that can be placed in the service of protecting and promoting human rights.